Sherlock holmes : the collector's edition of complete best novels / Sir Arthur Conan Doyle; penerjemah, Ismanto...[et.al] - DOYLE, Sir Arthur Conan; Ismanto (Indoliterasi, 2015)
739 hlm. : ilus. ; 24 cm.